2020
DOI: 10.1155/2020/8935694
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regulatory B Cell Subsets in Children with Type 1 Diabetes Mellitus

Abstract: B regulatory cells (Breg) refer to characteristic subsets of B cells that generally exert anti-inflammatory functions and maintain peripheral tolerance mainly through their ability to secrete interleukin-10 (IL10). Dysregulation in the function of Breg cells was reported in several autoimmune diseases. However, the relation between Breg and children with type 1 diabetes (T1D) is poorly understood. Thus, this study is aimed at determining whether Breg cells play a role in T1D in children or not, so we hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…( 32 ). Previous studies found a decrease of this regulatory B subset in T1D patients ( 33 35 ) suggesting that the lower frequencies of transitional B cells found in the present study could be related to an impairment in their regulatory properties. Moreover, here we show that patients at onset of the disease have higher percentages of naïve and IgM-only memory B cells, supporting that B cells can play a role in the pathogenesis of the disease, although more studies focusing on it are lacking.…”
Section: Discussionsupporting
confidence: 58%
“…( 32 ). Previous studies found a decrease of this regulatory B subset in T1D patients ( 33 35 ) suggesting that the lower frequencies of transitional B cells found in the present study could be related to an impairment in their regulatory properties. Moreover, here we show that patients at onset of the disease have higher percentages of naïve and IgM-only memory B cells, supporting that B cells can play a role in the pathogenesis of the disease, although more studies focusing on it are lacking.…”
Section: Discussionsupporting
confidence: 58%
“…It is clear that subsets, such as transitional CD24 hi CD38 hi B cells, enriched with IL-10 + B cells, decline with age ( 27 , 57 ), which is an important note for future studies. Recently, in children with type 1 diabetes, a decrease in both the CD24 hi CD27 + (B10) and transitional CD24 hi CD38 hi IL-10 + B cells but not in CD38 hi CD27 + IL-10 + plasmablasts was found ( 31 ). This numerical decrease was also negatively correlated with HbA1c levels ( 31 ), as was the frequency of CD24 hi CD38 hi B cells in a study by Wang et al.…”
Section: Impaired Regulatory B Cell Mechanisms In Type 1 Diabetesmentioning
confidence: 99%
“…Recently, in children with type 1 diabetes, a decrease in both the CD24 hi CD27 + (B10) and transitional CD24 hi CD38 hi IL-10 + B cells but not in CD38 hi CD27 + IL-10 + plasmablasts was found ( 31 ). This numerical decrease was also negatively correlated with HbA1c levels ( 31 ), as was the frequency of CD24 hi CD38 hi B cells in a study by Wang et al. ( 30 ).…”
Section: Impaired Regulatory B Cell Mechanisms In Type 1 Diabetesmentioning
confidence: 99%
“…A recent report from Sha et al revealed that IL-10-producing B cells prevent the development of diabetes in NOD mice via depleting the toll-like receptor 9 (TLR9) pathway [ 21 ]. In addition, El-Mokhtar et al reported lowered percentages of IL-10 + Breg cells in children with T1D [ 22 ]. Kleffel S et al reported an increase in IL-10 + Breg cells in the CD40 + B cells compartment that prevents β-cell destruction in NOD mice [ 23 ].…”
Section: Introductionmentioning
confidence: 99%